Path optimization algorithm and its robustness for bevel tip flexible needle. (2nd October 2018) - Zhang, Yong-De; Shi, Kai-Ming; Zhao, Yan-Jiang; Yang, Ji-Chao; Liu, Jia
Bevel tip flexible needle is a novel application in minimally invasive surgery, for it can avoid obstacles by performing a curved trajectory to reach the target. In clinical surgeries, path optimization is a basis for a robot-assisted surgery, and robustness is a crucial issue for an algorithm. However, to the best of our knowledge, none of the researches has an intensive study on the robustness of an algorithm for a bevel tip needle's path optimization. In this article, a path optimization algorithm for a bevel tip flexible needle is proposed based on a mathematical calculation method by establishing an optimization objective function, and the robustness of the algorithm is analyzed regarding to each weighting coefficient of the objective function. Simulation results show that on the one hand, the algorithm can obtain the optimal path effectively in the presence of obstacles; and on the other hand, the optimization function has little sensitivity to any of the weighting coefficients, verifying strong robustness of the algorithm. Experiments for three typical paths are performed, and the accuracy is within 2 mm which fulfills the surgical requirements. The experimental results not only prove the feasibility of the paths obtained by the algorithm but also verify the validity of the proposed path optimization algorithm.